Effects of acid pre-treatment on removal of organic and inorganic substances from Black Tilapia bones and scales - Sockalingam, Kanageswary; Hasan Zuhudi Abdullah,; Maizlinda Izwana Idris, (International Journal of Integrated Engineering, 2024)
Fish bones and scales are good sources of gelatin. However, high mineral content in bones and scales often lead to low quality gelatin with high percentage of ash. Therefore, pre-treatment with acid prior to gelatin extraction is necessary. Black tilapia (Oreochromis niloticus) bones and scales were subjected to 0 to 1.4 M HCl acid for 0 to 32 hr. The suitable pre-treatment conditions were determined using percentage of ash removed and loss of protein from the samples. Results obtained indicate, 99.86 % and 99.84 % of ash can be removed from bones and scales, with 1.4 M HCl (32 hr) and 1.0 M HCl (10 hr), respectively. Further analysis with UV-Vis revealed that, excessive protein breakdown starts to occur at 1.0 M (32 hr) and 0.6 M (12 hr), in bones and scales, respectively. The data suggest using pre-treatment conditions lower than the above to avoid protein loss which may lead to low gelatin yield.